TMJ alterations and their relationship with the appearance of dentofacial deformities: review of the literature (Research, Society and Development, 2023)
• Alterations in the temporomandibular joint have varied etiologies, and may negatively affect both the functionality and the facial aesthetics of the individual. The mandibular condyle, one of the main components of the TMJ, is an adaptive growth site that influences the final conformity of the face, therefore, the relationship between TMJ pathologies and dentofacial deformities is conspicuous. Therefore, the objective of this study is to explain changes in the temporomandibular joint, especially in the condyle region, and relate them to the appearance of dentofacial deformities. The present work was carried out through a narrative literature review based on articles indexed in SciELO, Google Scholar, PubMed and the Virtual Health Library. Scientific articles, master's thesis and books, published in the period from 2010 to 2022, in full, written in Portuguese, English and Spanish, were included, and works published before 2010 and that were unrelated to the topic addressed were excluded. Thus, 31 works were selected for the preparation of this work, where the TMJ changes that are related to the appearance of dentofacial deformities addressed in the present work are: hyperplasia, hypoplasia and condylar aplasia, osteoma, osteochondroma and ankylosis of the temporomandibular joint. Therefore, it was possible to perceive that the physiological development of the TMJ, especially that of the condylar structure, without any alteration that could harm it, such as trauma and infections, is essential to avoid conversion into dentofacial deformities.